Controlling coverage of solution cast materials with unfavourable surface interactions - Burlakov, V; Eperon, G; Snaith, H; Chapman, S; Goriely, A (2014)
Creating uniform coatings of a solution-cast material is of central importance to a broad range of applications. Here, a robust and generic theoretical framework for calculating surface coverage by a solid film of material de-wetting a substrate is presented. Using experimental data from semiconductor thin films as an example, we calculate surface coverage for a wide range of annealing temperatures and film thicknesses. The model generally predicts that for each value of the annealing temperature there is a range of film thicknesses leading to poor surface coverage. The model accurately reproduces solution-cast thin film coverage for organometal halide perovskites, key modern photovoltaic materials, and identifies processing windows for both high and low levels of surface coverage. © 2014 AIP Publishing LLC.